Agenesis of corpus callosum and optic nerve hypoplasia due to mutations in SLC25A1 encoding the mitochondrial citrate transporter. Issue 4 (7th February 2013) - Edvardson, Simon; Porcelli, Vito; Jalas, Chaim; Soiferman, Devorah; Kellner, Yuval; Shaag, Avraham; Korman, Stanley H; Pierri, Ciro Leonardo; Scarcia, Pasquale; Fraenkel, Nitay D; Segel, Reeval; Schechter, Abraham; et al.
Abstract : Background: Agenesis of corpus callosum has been associated with several defects of the mitochondrial respiratory chain and the citric acid cycle. We now report the results of the biochemical and molecular studies of a patient with severe neurodevelopmental disease manifesting by agenesis of corpus callosum and optic nerve hypoplasia. Methods and results: A mitochondrial disease was suspected in this patient based on the prominent excretion of 2-hydroxyglutaric acid and Krebs cycle intermediates in urine and the finding of increased reactive oxygen species content and decreased mitochondrial membrane potential in her fibroblasts. Whole exome sequencing disclosed compound heterozygosity for two pathogenic variants in the SLC25A1 gene, encoding the mitochondrial citrate transporter. These variants, G130D and R282H, segregated in the family and were extremely rare in controls. The mutated residues were highly conserved throughout evolution and in silico modeling investigations indicated that the mutations would have a deleterious effect on protein function, affecting either substrate binding to the transporter or its translocation mechanism. These predictions were validated by the observation that a yeast strain harbouring the mutations at equivalent positions in the orthologous protein exhibited a growth defect under stress conditions and by the loss of activity of citrate transport by the mutated proteins reconstituted into liposomes. Conclusions: We report for the first time a patient with a mitochondrial citrate carrier deficiency. Our data support a role for citric acid cycle defects in agenesis of corpus callosum as already reported in patients with aconitase or fumarate hydratase deficiency.